The logic of appeasement : can appeasement be a viable foreign policy option for the United States of America - Fang, Yi Shen (2019)
The policy of appeasement had long been dismissed as a viable policy option among foreign policy scholars and practitioners. This prompt dismissal stems from the misplaced notion that appeasement would only encourage continued aggression from the appeased. This paper argues that appeasement can and should be adopted against aggressor states that are motivated by insecurity by preventing the escalation of tensions and the outbreak of war. In contrast, a policy of confrontation should be used against aggressor states that are driven by greed, as appeasement would be unable to curb their expansionist policies. The intent of the state can be discerned through three indicators: the shifting of the balance of power, prestige and economic factors, and personality traits of the leader of the aggressor state. The theory mooted by this paper is corroborated by the examination of four case studies – Germany, Japan, Russia, and China.